Impact of Increased Postoperative Debridement Frequency following Functional Endoscopic Sinus Surgery. (23rd August 2013) - Manji, Jamil; Habib, Al‐Rahim; Wang, Jay C.C.; Gan, Eng C.; Hathorn, Iain F.; Javer, Amin R.
Abstract : Objectives: 1) Compare sinonasal‐specific quality of life between patients receiving an additional postoperative visit at 14 days compared to a standard of care control group receiving debridements at one, four, and twelve weeks post–functional endoscopic sinus surgery (FESS). 2) Compare endoscopically assessed mucosal edema between the two groups at one and three months post‐FESS to determine if the additional postoperative debridement had an impact on sinus health. Methods: Adult chronic rhinosinusitis patients receiving FESS at a tertiary‐level rhinology center between January 2011 and 2012 were included. Records were retrospectively evaluated for sinonasal outcome test (SNOT‐22) and mucosal edema scores (Philpott‐Javer) at one and three months post‐FESS. Treatment subjects receiving additional debridement fourteen days post‐FESS were compared to control subjects receiving the standard of care. Subjects were matched in terms of baseline disease severity and extent of surgery. Results: The cohort consisted of 48 subjects equally distributed between study groups. SNOT‐22 scores did not differ between the two groups at one and three months post‐FESS. These findings were not statistically significant (p=0.67, 95% confidence interval [CI]: ‐10.05, 15.47; p=0.63, 95% CI: ‐14.54, 8.96). The treatment group presented with greater reduction in mucosal edema between 1 and 3 months, although this was not statistically significant (3.29 vs. ‐0.26; p=0.40, 95% CI: ‐4.83, 11.93). Conclusions: Additional postoperative debridement within the first month following FESS did not provide a significant improvement in quality of life and mucosal edema. However, a clinically significant improvement in mucosal edema was observed with the additional debridement.